ANALYSIS OF MONETARY FACTORS ON THE INCOME OF COASTAL FISHERMAN’S IN THE COVID-19 WEST ACEH REGENCY - Leli Putri Ansari; Ivon Jalil; Yasrizal Yasrizal (Teunuleh Publisher, 2021)
This research aimed to analyze fisherman’s income according to monetary factors during covid-19 pandemic in coastal areas of West Aceh Regency in Aceh Province, Indonesia. This research applied cross-section data over 2021 by utilizing descriptive quantitative research and OLS model analysis (Ordinary Least Square). Research revealed monetary factors in term of the inflation of groceries price had negative influenced to the fisherman income at West Aceh Regency, mean while the variable of diesel price had positive influenced to fisherman income. During covid-19 pandemic, there was the increasing of groceries price (inflation) at 1,06 times or the consumer price index (CPI) of groceries price at 106 percent but the price of diesel was still same as before covid-19 pandemic because fisherman used subsidized fuel at Rp 5.150/liter. However, the quota of subsidized diesel did not fulfill the fisherman needs so that they must buy non subsidized diesel. It was impacted on the fishing operational cost which was bigger than fisherman income. Moreover, during covid-19 pandemic the average of fisherman income decrease at IDR 1.500.000-IDR 3.000.000 each trip compared with before covid-19 pandemic at IDR 5.000.000- IDR 7.000.000 each trip. It was caused by low fish price which was caused by the decreasing of fish demand.